2011
DOI: 10.1038/ismej.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

Depleted dissolved organic carbon and distinct bacterial communities in the water column of a rapid-flushing coral reef ecosystem

Abstract: Coral reefs are highly productive ecosystems bathed in unproductive, low-nutrient oceanic waters, where microbially dominated food webs are supported largely by bacterioplankton recycling of dissolved compounds. Despite evidence that benthic reef organisms efficiently scavenge particulate organic matter and inorganic nutrients from advected oceanic waters, our understanding of the role of bacterioplankton and dissolved organic matter (DOM) in the interaction between reefs and the surrounding ocean remains limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
123
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 85 publications
22
123
3
1
Order By: Relevance
“…However, these observations are in contrast to a previous work demonstrating significant differences in microbial community composition between sample sites on coral reefs at Lizard Island (GBR), Magnetic Island (GBR) and Tobago (Caribbean) [14,16,26]. Nelson et al [27] examined the spatio-temporal variations throughout Paopao Bay (French Polynesia) by measuring changes in the community composition between waters from the bay, the reef and the open ocean, revealing distinctly different phylogenetic features of the bacterial communities between sites. The microbial communities inhabiting healthy, diseased and bleached Acroporas from American Samoa and the Great Barrier Reef have also recently been shown to demonstrate compositional shifts under natural bleaching and disease events, with the abundance of Vibrio bacteria increasing during bleaching [28,29].…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, these observations are in contrast to a previous work demonstrating significant differences in microbial community composition between sample sites on coral reefs at Lizard Island (GBR), Magnetic Island (GBR) and Tobago (Caribbean) [14,16,26]. Nelson et al [27] examined the spatio-temporal variations throughout Paopao Bay (French Polynesia) by measuring changes in the community composition between waters from the bay, the reef and the open ocean, revealing distinctly different phylogenetic features of the bacterial communities between sites. The microbial communities inhabiting healthy, diseased and bleached Acroporas from American Samoa and the Great Barrier Reef have also recently been shown to demonstrate compositional shifts under natural bleaching and disease events, with the abundance of Vibrio bacteria increasing during bleaching [28,29].…”
Section: Introductioncontrasting
confidence: 55%
“…Previous research has used metagenomics to reveal large changes in microbial community composition and function between different coral reefs [18,19]. However, while 16S rRNA-based approaches have shown that microbial community composition can shift within reef systems [14,16,26,27], patterns in microbial functional potential across different niches within a single coral reef ecosystem had not previously been documented.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they included species-specific bacterial components of the coral holobiont (1), as well as specific bacterial taxa associated with some algal functional groups (1,25). In addition, the microbial communities sampled on these reefs reflected selection by the adjacent benthic macroorganisms, as evidenced by the differences between reef-associated bacterioplankton communities and open ocean communities (26). There is evidence that reef-associated communities undergo selection in shallow reef environments by the locally available labile organic matter exuded by the benthic organisms (27).…”
Section: Discussionmentioning
confidence: 99%
“…4). Although it is widely accepted that depth is an important factor in controlling the vertical distribution of bacteria in the soil and in the water column (38,43), our emphasis in this study is on the role of depth in a landscape, rather than along a vertical column.…”
Section: Discussionmentioning
confidence: 99%